Economic Interdependence and the International Implications of Supply-Side Policies. (IMF Working Papers; Working Paper ;, 1989)
This paper evaluates the effect of foreign debt on investment in a heavily-indebted country, using numerical simulations of a simple rational expectations growth model. Two particular effects are distinguished. First, the effect due to 'debt overhang' of past accumulated debts; and second, the effect of 'credit rationing' or inability to obtain new financing. The results from the simulations indicate the credit rationing may be a powerful disincentive to investment. This suggests that in order to maximize the impact on productive investment, debt reduction plans need to be accompanied by additional foreign lending.